Ice cover and partner removal increase movements of invasive mesopredator in the coastal island mosaic - Toivonen, Pyry; Toivola, Mikko; Selonen, Vesa (John Wiley & Sons, 2025)
The invasion of new areas is influenced by landscape structure, seasonal conditions and social interactions. Coastal and lake landscapes pose unique challenges for land animals due to water barriers, while the ice cover in northern latitudes can facilitate movement. For invasive alien species, information on movement capabilities provides data for management. This study examines the movement patterns of an invasive mesopredator, raccoon dog, in a fragmented coastal environment in southwestern Finland to better understand its movement capabilities and potential expansion. Using GPS tracking, we investigated individual movements between islands, considering the role of ice cover, island connectivity and social interactions (partner removal by management). The raccoon dog has low winter activity levels, but our findings demonstrate that the individuals remain active during the cold season and use ice cover to reach islands perhaps otherwise unreachable. The number and connectivity of islands also play a crucial role in movement distances. Moreover, the partner removal increases movement between islands during the summer. We conclude that the raccoon dog is highly mobile in the coastal landscape, with ice cover facilitating movements between islands. Practical implication. To effectively manage this invasive species, creating single individuals should be avoided before avian breeding season. This strategy can help prevent solitary raccoon dogs from wandering and potentially colonizing new areas. Melting ice due to climate change is often mentioned as a benefit to invasive species, but our results provide an example of where the ice cover potentially enhances movement of an invasive species and thus requires consideration.
Keywords: supikoira; raccoon dog; saaristo; vieraslajit; invasive species; coast; dispersal; inter-island movement; mesopredator; overwater movement